The effect of sensation seeking and emotional brand attachment on consumers' intention to consume risky foods in restaurants. Issue 3 (27th May 2017) - Kim, Jooho; Almanza, Barbara; Ghiselli, Richard; Sydnor, Sandra
ABSTRACT: Sensation seeking and emotional brand attachment have been studied extensively, but limited research has been conducted on "risky foods." This study explored how sensation seeking, emotional brand attachment, and risky food consumption varies demographically, and the relationships among those variables. Approximately 300 responses were collected from a restaurant serving "risky" and "nonrisky" foods. Significant differences included that consumption of raw/undercooked fish/eggs was higher in younger groups. Females showed more affection toward emotionally attached restaurants. The hypotheses testing showed the positive relationship from sensation seeking and emotional attachment to risky food consumption. Results offer information about marketing to different demographic groups.